(1596) A New Approach for Pricing Agricultural Land in Egypt Considering Policy reforms and environmental concepts نهج جديد لتسعير الأراضي الزراعية في مصر مع مراعاة إصلاحات السياسات والمفاهيم البيئية - El Wahab, Nagwan S.Abd. (The Institute of National Planning, 2018)
Includes bibliographical references.